Pembuatan Rangka Atap dan Sarana Pendukungnya Bangunan Pengolah Sampah Desa Banjararum Kalibawang - Bambang Herumanta (Pengabdian dan Pengembangan Masyarakat Sekolah Vokasi UGM, 2018)
Garbage in Banjararum is increasing due to the source of garbage that always increases. The source of garbage comes from stalls, schools, health centers, and agriculture. To handle the garbage needs a solution to reduce the negative impact on health society. Implementation is carried out with stages, measurements, installation of stakes, excavation of foundation, installation of roof, installation of columns, walls, roof truss, and roof cover. Followed by making a machine room, pools to collect the garbage. The results of this community service are that the garbage processing building consists in the engine room, Pools for garbage collection that will be processed.